Major dietary patterns among female adolescents with eating disorders: a factor analysis approach - Roustaee, Roshanak; Hajifaraji, Majid; Djazayery, Abolghasem; Mehrabi, Yadollah (Progress in Nutrition, 2018)
Aim: Present study was conducted to determine major dietary patterns among female students as major factors in preventing eating disorders. Methods and Material: In this cross-sectional study, 515 samples were detected through 2766 female students who were selected by a multistage random sampling from 5 distinct of Tehran and assessed for having eating disorders. A two-stage procedure including screening using Eating Attitude Test-26 questionnaire and a semi structured questionnaire based on Diagnostic & Statistical Manual of Mental disorders, 4th ed. diagnostic criteria was used to diagnose eating disorders. All participants fulfilled a modified version of the Body Shape Satisfaction Scale and a qualitative food frequency questionnaire. Dietary patterns were defined using factor analysis and three interpretable factors were obtained. Then, people were categorized based on their dietary patterns’ scores quartiles. To identify the association between dietary patterns and eating disorders, logistic regression was used in three models. Findings: Using factor analysis, three major dietary patterns were obtained: High carbohydrate- High fat pattern, High Proteins- High fat pattern and High Fibre-Low fat pattern. Findings showed that the Odds ratio of eating disorder reduced in high protein- high fat pattern and after adjustment of confounding factors, this reduction is still remained significant. Odds ratio of eating disorder is increased in high fibre- low fat dietary pattern significantly in all models. Conclusions: It seems that odds of eating disorders is higher in adolescents who follow a high fibre – low fat (vegetarian) dietary pattern and lower in adherence to “high protein-High fat” dietary pattern.